The Nature of Science and Knowledge in The Philosophy of Science - Dahlan, Dewi; Najmuddin, Najmuddin; Buerangae, Firdow; Selamat, Kasmuri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This research describes the nature of science and knowledge in the study of the philosophy of science. Philosophy of science involves search and exploration in the development of philosophical concepts about knowledge. Scientific knowledge manifests itself through various interrelated dimensions. Philosophy is a human thinking activity that aims to find the causes of everything and to understand how humans act after gaining this knowledge. This research uses the Library Research method. Literature study is a study used to collect information and data. The results of scientific research are knowledge that is rational, systematic, comprehensive, consistent and general. Knowledge, on the other hand, is the totality of all knowledge that is not yet well organized, both in metaphysical and physical terms. Knowledge tends to be general information based on experience and habits, without specific methods and mechanisms.